2015
DOI: 10.1016/s1473-3099(15)70090-3
|View full text |Cite|
|
Sign up to set email alerts
|

Presence of Middle East respiratory syndrome coronavirus antibodies in Saudi Arabia: a nationwide, cross-sectional, serological study

Abstract: European Union, German Centre for Infection Research, Federal Ministry of Education and Research, German Research Council, and Ministry of Health of Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
319
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(342 citation statements)
references
References 22 publications
18
319
4
1
Order By: Relevance
“…In a recent cross-sectional seroprevalence study that included 10 009 subjects in Saudi Arabia, the presence of antibodies against MERS-CoV was found to be 23 times higher (3.6% vs 0.15%, p<0.001) in slaughterhouse workers who are occupationally exposed to camels than in the general population [3]. The authors note that the higher prevalence in young males observed in this study is an indication of unrecognised infections with mild or no symptoms.…”
Section: Recent Evidencementioning
confidence: 41%
“…In a recent cross-sectional seroprevalence study that included 10 009 subjects in Saudi Arabia, the presence of antibodies against MERS-CoV was found to be 23 times higher (3.6% vs 0.15%, p<0.001) in slaughterhouse workers who are occupationally exposed to camels than in the general population [3]. The authors note that the higher prevalence in young males observed in this study is an indication of unrecognised infections with mild or no symptoms.…”
Section: Recent Evidencementioning
confidence: 41%
“…Saudi Arabian communities still lack awareness of recommended protective measures that help prevent the transmission of the virus (14). It is estimated that 44 951 individuals older than 15 years may be seropositive for MERS-CoV in Saudi Arabia, and may be a source of infection for patients who have not been exposed to camels previously (15). A positive correlation has been demonstrated between contact with infected persons and infection risk, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…2 Dromedary camels serve as an important reservoir host involved in transmission to humans, Human-to-human transmission was confirmed in 2013. [3][4][5] Globally, since September 2012, 1952 laboratory-confirmed infected cases with MERS including at least 693 related deaths have been reported to WHO from 27 countries. Approximately 80% of human cases have been reported by Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%